PKM Kelompok Pembudidaya Ikan Di Kelurahan Tendeki Kecamatan Matuari Kota Bitung Provinsi Sulawesi Utara - Mudeng, Joppy D.; Longdong, Sammy N. J. (e-Journal BUDIDAYA PERAIRAN, 2019)
"Gemusis" fish cultivation group is one of the aquaculture business groups that exist in Tendeki Village, Matuari District, Bitung City, North Sulawesi Province. The width of Â pond owned is around 3 ha with an average production of 2 tons per year. The main problem in this group is the difficulty in obtaining superior seeds, expensive feed prices and often the fish that are kept stricken with disease, resulting in less production and even crop failure. Alternative solutions to problems in partner problems are accompanied by two approaches, namely the classical and individual approaches. The classical approach is carried out when delivering the material. An individual approach is taken at the time of practice. Lectures in class in the form of delivery of how to make tilapia seed with sex reversal methods for the maintenance of monosex, making low-quality quality feed made from local raw materials and producing maggot as natural food, as well as how to increase fish immunity by giving immunostimulants to fish feed. Demonstration and practice with techniques for making cheap feed ingredients made from local raw materials. In order for the fish cultivation activities carried out by the partners according to the activity plan, monitoring and assistance will be carried out after the lecture and practice activities. The results obtained showed the group are able to cultivate fish with monosex system, produce feed using local raw materials, maggot cultivation as a natural feed, and can treat fish diseases using mmunostimulant.